Investigasi Penyakit Busuk Ujung Lancip Buah Salak pada Rantai Pasok - Jamaludin Jamaludin; Lilik Pujantoro Eko Nugroho; Emmy Darmawati (Jurnal Keteknikan Pertanian, 2018)
AbstractSalak fruit (Salacca edulis Reinw.) which is not handled properly during distribution and marketing will be damaged. The biggest damage caused by rot disease on the taper tip of the fruit, which has an impact on postharvest losses and market rejection. The aims of this study were to examine supply chain pattern of salak pondoh, rot disease causative microorganisms on the salak's taper tip and the magnitude of postharvest losses due to the rot disease. Data were collected by survey method to obtain the pattern of supply chain and postharvest losses rate. Surveys (interviews and observations) were conducted in each of the supply chain actors at salak pondoh production centers, Sleman Regency, Yogyakarta. Laboratory observations to identify disease causative microorganisms were conducted using single spore isolation method on the PDA and fungi morphological observations. The results of the investigation of supply chain patterns in Sleman Regency, in general, there are three patterns, namely supply chain for the distribution of traditional markets, modern markets, and export markets. Total postharvest losses along those supply chains were 22.89%, 11.27%, and 6.26%, respectively. The results of isolation were obtained five fungus isolates, namely Thielaviopsis paradoxa (De Seynes) Honhel (58.4%) Colletotrichum gloeosporioides section (19.48%), Rhizopus stolonifer (Ehrenberg) Vuillemin (15.58%), Mucor sp. (3.90%), and Mycelia sterilia (2.60%). Based on the level of findings, the fungus Thielaviopsis paradoxa was the main causative microorganisms of rot disease on the salak pondoh's taper tip.AbstrakBuah salak (Salacca edulis Reinw.) yang tidak ditangani dengan baik selama distribusi dan pemasaran akan rusak. Kerusakan terbesar adalah karena penyakit busuk ujung lancip buah salak yang berdampak pada kehilangan pascapanen dan penolakan pasar. Tujuan penelitian ini ialah mengkaji pola rantai pasok salak pondoh, jenis mikroorganisme penyebab penyakit busuk ujung lancip buah salak, dan besarnya tingkat kehilangan pascapanen yang disebabkannya. Pengumpulan data dilakukan dengan metode survei untuk memperoleh pola rantai pasok salak pondoh dan tingkat kehilangan pascapanen. Survei (wawancara dan observasi) dilakukan di setiap pelaku rantai pasok di sentra produksi salak pondoh, Kabupaten Sleman, Yogyakarta. Pengamatan laboratorium untuk mengidentifikasi mikroorganisme penyebab penyakit dilakukan dengan metode isolasi spora tunggal pada PDA dan pengamatan morfologi cendawan. Hasil investigasi pola rantai pasok di Kabupaten Sleman secara umum terdapat tiga pola yaitu rantai pasok untuk distribusi pasar tradisional, pasar modern dan pasar ekspor. Total kehilangan pascapanen sepanjang rantai pasoknya masing-masing adalah 22.89%, 11.27%, dan 6.26%. Hasil isolasi diperoleh lima isolat cendawan yaitu Thielaviopsis paradoxa (De Seynes) Honhel (58.4%), Colletotrichum gloeosporioides section (19.48%), Rhizopus stolonifer (Ehrenberg) Vuillemin (15.58%), Mucor sp. (3.90%), dan Mycelia sterilia (2.60%). Berdasarkan besarnya tingkat temuan, cendawan Thielaviopsis paradoxa merupakan mikroorganisme penyebab utama busuk ujung lancip buah salak pondoh.